Local composition detouring for defect-free compositionally graded materials in additive manufacturing. Issue 7 (3rd July 2023) - Kim, Eun Seong; Park, Jeong Min; Karthik, Gangaraju Manogna; Kim, Kyung Tae; Yu, Ji-Hun; Lee, Byeong-Joo; Kim, Hyoung Seop
Abstract : This study investigated cracking phenomena in 316L stainless steel (SS316L) and Inconel 718 (IN718) composition-graded material (CGM) additively manufactured by the direct energy deposition (DED) process. In order to prevent cracking in the CGM, thermodynamic analysis was performed to avoid the critical concentration for crack formation. Based on the local compositional detouring (LCD) method suggested by new approach, a crack-free CGM with a nonlinear combination of SS316L and IN718 was successfully fabricated with local additional elemental powder in the CGM defective region obtained using a multi-powder feeding system during the DED process. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: We aim to avoid the cracks of functionally graded materials fabricated by local in-situ alloying technique using the result of thermodynamically analyzing.